2001
DOI: 10.1002/jcla.1038
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of baseline erythropoietin (EPO) level and corrected reticulocyte count as an indicator for a favourable response to recombinant human erythropoietin (rhEPO) therapy in anaemic cancer patients

Abstract: Our study suggested that the baseline ratio of EPO/ret.count should be used as an indicator for a favourable response to rhEPO therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It can represent the responder and non-responder of the erythropoietic activity of the bone marrow; high level of EPO/% retic ratio means non-responder patients while low level of EPO/% retic ratio means responders [37]. From Table 4 and Fig.…”
Section: Epo/% Reticulocyte Ratio Reticulocyte Index and Reticulocytmentioning
confidence: 95%
“…It can represent the responder and non-responder of the erythropoietic activity of the bone marrow; high level of EPO/% retic ratio means non-responder patients while low level of EPO/% retic ratio means responders [37]. From Table 4 and Fig.…”
Section: Epo/% Reticulocyte Ratio Reticulocyte Index and Reticulocytmentioning
confidence: 95%
“…A more recent study claims that the ratio of baseline serum EPO and corrected reticulocyte count accurately predicts EPO response in 78% of cases. 38 Other patient characteristics, such as diagnosis, type and duration of cancer treatment, bone marrow involvement, or solid tumor vs hematologic malignancy, were not useful indicators of predictable response to EPO.…”
Section: Patient Selectionmentioning
confidence: 93%
“…Ludwig et al [50], in a mixed sample of solid (43) and nonsolid (37) tumor patients, observed a significant inverse correlation (r = -0.265) between baseline eEPO level and response to rHuEPO, with an optimal cutoff point of 100 mU/ml for predicting response. Charuruks et al [2] found that a low eEPO level and a high corrected reticulocyte count might be predictors of favorable response to ESA.…”
Section: The Role Of Serum Eepo Levels As Predictors Of Response To Esamentioning
confidence: 98%
“…Four weeks must elapse before response to ESA can be detected. It takes 2 weeks for erythroid burst-forming units (BFU-E) to form and another 2 weeks for the erythroblasts to turn into erythrocytes [2].…”
Section: Erythropoiesis-stimulating Agents: Responders and Nonrespondersmentioning
confidence: 99%
See 1 more Smart Citation